Theory of Pollution Certificates: Policy Developments and Industrial Applications (Global Journals of Research in Engineering, 2013)
A mathematical applicability test is carried out in this paper. The Pollution Certificate Theory is evaluated for an industrial cluster in Brazil. The purpose here is to discuss the contributions made by environmental agencies in controlling water pollutant emissions. This is considered by means of an instrument associated with economic regulatory instruments (as used in Brazil). A scenario is designed for an Industry Cluster with five industries and a potential to cause water pollution by the release of organic waste. In the test it is considered that the effluent is released in a Class II river, according to Brazilian CONAMA Resolution (no. 357). The marginal costs of abatement are arbitrated, whilst the reductions necessary to achieve the environmental targets were calculated. The control costs comparison and the use of standard emissions with the utilization of Pollution Certificates led to the conclusion that the Pollution Certificate Theory is a beneficial tool for water management issues, as it meets the environmental requirements at a lower abatement cost in industrial activities.
Keywords: pollution certificates; pollution credits; pollution certificate